Type B CpG oligodeoxynucleotides induce Th1 responses to peanut antigens: Modulation of sensitization and utility in a truncated immunotherapy regimen in mice. Issue 5 (5th February 2013) - Kulis, Mike; Gorentla, Balachandra; Burks, A. Wesley; Zhong, Xiao‐Ping
<x xml:space="preserve">Abstract</x> Scope Peanut allergy stems from a Th2‐biased immune response to peanut allergens leading to IgE production and allergic reactions upon ingestion. Methods and results A model of peanut allergy in C3H/HeJ mice was used to assess whether type A, B, or C CpG oligodeoxynucleotide (ODN) molecules would be effective in: (i) a prophylactic approach to prevent peanut allergy when administered simultaneously with a Th2‐skewing adjuvant, and (ii) a therapeutic model to allow for shortened immunotherapy. Type B ODNs were extremely effective in inhibiting anaphylaxis in the sensitization protocol as evidenced by differences in symptom scores, body temperature, and mouse mast cell protease 1 release compared to sham treatment. In the therapeutic model, co‐administration of type B ODN plus peanut proteins was highly effective in reducing anaphylactic reactions in mice with established peanut allergy. The therapeutic effect was accompanied by an increase in IFN‐γ and peanut‐IgG2a, without a significant decrease in peanut IgE or IL‐4 responses. Conclusion CpG ODNs, especially type B, were highly effective in inducing Th1 responses in mice undergoing induction of peanut allergy, as well as in mice undergoing therapy for established peanut allergy. Interestingly, the IgE response was not significantly altered, suggesting that IgG antibodies may be enough to prevent peanut‐induced anaphylaxis.